(untitled) (Baghdad Science Journal, 2008)
The huge magnetic fields of neutron star cause the nuclei of the stellar surface to form a tightly bound condensed layer. In this research some characteristics of polar gap and magnetosphere enclosed the star according to Sturrock Model were illustrated, positrons move out along the open field lines, and electrons flow to the stellar surface as in the related to Sturrock model. The magnetic field within polar gap areas, which is defined by the Irvin Radius (RL) decreases due to the expansion of the polar, resulting from the physical motion of the accreted material. The values of height gap at different distances from the star were estimated. The obtained results improve the most energetic positrons those with E? Emax radiate away their energy in a distances re = 104m above the polar gap while less energetic positrons produced at much greater distances re =108m. The potential drop across the polar gap is obtained using a well defined adopted formula, it is found that the potential drop across the polar gap grows like (h2), when h « rp